PENGARUH KONSENTRASI SERBUK EKSTRAK DAUN KELOR (Moringa Oliefera Lam) DAN TINGKAT KEHALUSAN BAHAN TERHADAP KARAKTERISTIK MINUMAN INSTAN SERBUK KACANG HIJAU (Vigna radiata L) - hasnelly sriyono (Pasundan Food Technology Journal (PFTJ), 2018)
The purpose of this research to study the effect of the concentration of Moringa leaf powder extract and degree of fineness of materials on the instant beverage powder green beans.This research uses experimental design factorial 3x3 in ranangan randomized (RAK) in a repeat 3 times, where the factors include: the effect of the concentration of pollen extract of leaves of Moringa (K), which consists of three levels, namely k1 (5%), k2 (10% ), k3 (15%) and the degree of fineness of the material (T), which consists of three levels: t1 (60mesh), t2 (80mesh), t3 (100mesh).The response in this study is a chemical response, ie protein content, moisture content. Physical response that total dissolved solids (TSS). Response organoleptic including color, aroma, taste, and consistency and test the antioxidant activity in the selected sample.Moringa leaf powder extract concentration significantly affected the water content of the instant beverage powder green beans. Degree of fineness of materials significantly affect total soluble solid instant beverage powder green beans. The interaction between the concentration of Moringa leaf powder extract and degree of fineness of materials does not affect the organoleptic tests include color, flavor, aroma, consistency, and chemical responses include water content, protein content and physical response that total dissolved solids in the instant beverage powder green beansBased on the chemical analysis and fisica analysis showed that the treatment was selected on the instant beverage powder green beans are k3t3 concentration of Moringa leaf powder extract (15%) and the degree of fineness of materials (100mesh) with a total value of 5.87°Brix dissolved solids, water content of 8.18%, protein content 20,34% and amounted to 186014 ppm antioxidant activity.